Perceptions of Indonesian teachers on the implementation of “Merdeka” Curriculum - Zamista, Adelia Alfama; Deswita, Pipi (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
Abstract: The Merdeka Curriculum is a curriculum that has just been widely implemented in Indonesia as a substitute for the 2013 Curriculum. This curriculum aims to improve the quality of learning implementation in Indonesia. The teacher is always the spearhead of a curriculum. Because teachers design learning and interact directly with students. This study aims to see how teachers perceive the Independent Curriculum, which is a new curriculum in Indonesia. The research method used is a systematic literature review. The results of the literature review show that in general teachers have a positive perception of the Independent Curriculum, because teachers are aware of the potential of the Independent Curriculum in improving the quality of learning. But furthermore, for teacher readiness to apply the Independent Curriculum, such as planning, implementing learning, and conducting assessments, it turns out that the teacher's perception is still in the sufficient category. Teachers still need various trainings to improve their knowledge and skills in implementing the Independent Curriculum.